An annotated checklist of the endemic Apiaceae of Kazakhstan - Kljuykov, Eugene; Lyskov, Dmitry; Ukrainskaja, Uliana (Phytotaxa, 2018)
An annotated checklist of the endemic Apiaceae species of Kazakhstan includes synonyms, references, geographic distributions, ecological preferences and distribution maps for each species. The number of endemic Apiaceae species in Kazakhstan is reduced from 63 to 29 because of their localities discovered in neighboring countries or because of their placement into synonymy. Two new synonyms are proposed here, to include Dorema karataviense into D. sabulosum and Prangos arenaria into P. cachroides. The Karatau Range and its vicinities are the main center of endemism of the Apiaceae in Kazakhstan. Many endemics are also found in the Dzungarian Alatau Range and the Tarbagatai Range. Most of the endemics can be considered neoendemic species; their evolution took place in geographical isolation.